(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Zigbee technology has emerged as a significant player in the realm of wireless communication protocols, catering to the expanding landscape of the Internet of Things (IoT) and smart device ecosystems. Designed to address the unique requirements of low-power, short-range communication, Zigbee offers a robust platform for establishing interconnected networks of devices. This abstract provides an overview of Zigbee technology, focusing on its key features, architecture, applications, and advantages.